2012
DOI: 10.1242/jcs.098020
|View full text |Cite
|
Sign up to set email alerts
|

Ligand oligomerization state controls Tie2 receptor trafficking and Angiopoietin-2 ligand-specific responses

Abstract: SummaryAngiopoietin 1 (Ang1) is an activating ligand for the endothelial receptor tyrosine kinase Tie2, whereas Ang2 acts as a contextdependent agonist or antagonist that has a destabilizing effect on the vasculature. The molecular mechanisms responsible for the versatile functions of Ang2 are poorly understood. We show here that Ang2, but not Ang1, induces Tie2 translocation to the specific cell-matrix contact sites located at the distal end of focal adhesions. The Ang2-specific Tie2 translocation was associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 52 publications
3
20
0
Order By: Relevance
“…Interestingly, it has been shown previously that after activation, Tie2 forms clusters at cell-cell contacts in confluent cells where it regulates endothelial cell permeability and also has been shown to localize at the trailing edge of migrating cells. 13,44 We now show that during collective migration, Tie2 clusters form at the leading edge of leader cells but do not colocalize with adherens junction proteins or PKC, similar to what has been observed at cell junctions. 13 This suggests that distinct signaling events must emerge from Tie2 to promote the formation of ␤-catenin/PKC complexes at cell junctions and for the localization of polarity and adherens junction proteins at the leading edge.…”
Section: Discussionsupporting
confidence: 72%
“…Interestingly, it has been shown previously that after activation, Tie2 forms clusters at cell-cell contacts in confluent cells where it regulates endothelial cell permeability and also has been shown to localize at the trailing edge of migrating cells. 13,44 We now show that during collective migration, Tie2 clusters form at the leading edge of leader cells but do not colocalize with adherens junction proteins or PKC, similar to what has been observed at cell junctions. 13 This suggests that distinct signaling events must emerge from Tie2 to promote the formation of ␤-catenin/PKC complexes at cell junctions and for the localization of polarity and adherens junction proteins at the leading edge.…”
Section: Discussionsupporting
confidence: 72%
“…We show that Tie1/Tie2 heterodimerization may involve interactions between the Fn3 domains, but it is not clear how Tie1 interacts with the arrays of Tie2 homodimers in trans or how angiopoietins bridge Tie2 association across EC-EC junctions. The context-dependent differences in angiopoietin-activated Tie2 signaling pathways may depend on differences in other subcellular protein constituents, such as integrins in the ECM contacts and VE-PTP in EC-EC contacts (10,13,19,47). Further structural and functional investigation is required to understand how Tie1 acts to modulate the effects of Ang1 and Ang2 on Tie2 and the mechanism of Ang2 antagonism in the Tie2 trans association.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, angiopoietin 2 modulates the endothelial receptor tyrosine kinase Tie2 and induces Tie2 translocation to the specific cell-matrix contact sites located at the distal end of focal adhesions. It is reported that the different oligomeric/multimeric forms of the angiopoietins cause induction of distinct patterns of Tie2 trafficking (68). Similarly phosphorylation and dimerization regulate nucleocytoplasmic shuttling of mammalian STE20-like kinase (69).…”
Section: Discussionmentioning
confidence: 99%